ET-55 THE LONG TERM RISK OF TUMOR PROGRESSION HAS NOT CHANGED OVER TIME FOR SUPRATENTORIAL GRADE II GLIOMAS AND IS NOT INFLUENCED BY THE MODE OF SURGICAL TREATMENT - Schnell, Oliver (Oxford University Press, 2014)
BACKGROUND: To determine the risk pattern of tumor progression over time in supratentorial WHO grade II gliomas, we compared long term outcome either after stereotactic iodine brachytherapy (SBT) or open tumor resection (OTR). The stereotactic group has been treated predominantly in the CT-era, whereas the resection group exclusively referred to the MR-era. PATIENTS AND METHODS: The SBT (OTR) group consisted of 239 (123) adult patients with histologically proven supratentorial WHO grade II (oligo-)astrocytomas undergoing first treatment between 1979-1992 (1991-1998). Adjuvant treatment was always withhold until tumor progression occurred. Primary endpoints were time to tumor progression (PFS) according to the Macdonalds criteria and time to malignant transformation (MTT). Secondary endpoint was survival (OS). Endpoints were estimated with the Kaplan Meier method, prognostic factors were obtained from proportional hazards models. RESULTS: The SBT and OTR group did not differ in terms of age and Karnofsky scores; tumors were smaller (p < 0.001), more often deep seated (p < 0.001) and left sided (p < 0.01) in the SBT group. Median follow up for survivors after SBT (OTR) was 10.5 years (14 years). 5- and 10-years PFS rates were 50% and 25% in the OTR group and 42% and 23% in the SBT group (p = 0.2). 5- and 10-years MTT rates were 32% and 60% in the OTR group and 32% and 54% in the SBT group (p = 0.7). There was no leveling-off of the curves in any of the analyzed groups. OS was longer in the OTR group; but in multivariate models, OTR was not superior to SBT regarding PFS and MTT. CONCLUSION: Risk patterns of tumor progression in supratentorial grade II (oligo-) astrocytomas are still dominated by the natural course of the disease. Longer survival after resection might indicate improvement of salvage treatment concepts over time after tumor progression.